Bolivia Systematic Country Diagnostic : Rebalancing Inclusive Growth to Deepen Gains on Poverty and Inequality Reduction - World Bank Group (World Bank, Washington, DC, 2016)
The objective of this Systematic Country Diagnostic (SCD) is to identify the priority constraints Bolivia faces in sustaining its gains on reducing poverty and enhancing shared prosperity over the next years. It will analyze the dynamics behind the progress achieved in the past decade on inclusive growth, and identify a number of key constraints for sustaining and consolidating this progress. The SCD begins, in Chapter two, with a presentation of four characteristics that make Bolivia special, including its State‐led development strategy, large natural resource wealth, difficult geography and landlocked condition, and rich ethnic diversity. In chapter three, this SCD presents an in‐depth evaluation of the generally positive evolution in growth and in the reduction of poverty and inequality over the past decade. An assessment of the recent past and current context concludes that there is a need for enabling new inclusive growth engines, particularly through increased private investment and higher productivity. Chapter four makes a case for rebalancing the path of inclusive growth, and presents three main challenges in this sense: sustaining macroeconomic and fiscal stability, developing non‐extractive sectors with higher productivity and a lower environmental footprint, and reducing gaps and disparities in access to opportunities. The discussion of these challenges reveals a number of priority constraints, a key input for the prioritization exercise. Finally, in chapter five the SCD presents the findings of a prioritization exercise aimed at producing a restricted list of prioritized constraints, as well as a list of knowledge gaps identified in the different parts of the analysis.